The Influence of Presence and Position of Women on the Boards of Directors: The Case of NHS Foundation Trusts - Ellwood, Sheila (Journal of business ethics, 2015)
This study examines the influence of women on the boards of directors of National Health Service Foundation Trusts (FTs) in England. FTs provide a public service where social performance is the primary objective, although financial constraints must be met. Female presence (the proportion of women) is higher for executive directors than non-executives, reflecting the high number of women employed in the sector. We find that a high female presence among executive and non-executive directorships does not result in significant differences either in financial return or service quality. When gender diversity on boards is consistently high (high level of female presence across boards), the benefits on performance of having more women on the board may not be discernible. However, female Chairs or Chief Executives result in significant reductions in negative social outcomes, such as lower clinical negligence costs, without harming financial management. The findings of this study, carried out in a context of high female presence and where a woman frequently occupies one of the two most influential board positions, Chair and Chief Executive, have implications for gender diversity and gender targets on the boards of directors in business and other sectors.